First investigation of modified poly(2-vinyl-4, 4-dimethylazlactone)s as kinetic hydrate inhibitors. (2nd October 2016) - Ree, Lilian H.S.; Kelland, Malcolm A.; Roth, Peter J.; Batchelor, Rhiannon
Abstract: A series of polymers of 2-vinyl-4, 4-dimethylazlactone (VDMA) of varying molecular weights modified with small organic amines have been synthesized. Their performance as kinetic hydrate inhibitors (KHIs) has been investigated in high pressure steel rocking cells using a Structure II-forming synthetic hydrocarbon gas mixture. It was found that the PVDMA polymer with the lowest molecular weight (Mn =1845 g/mole by 1 H NMR) performed the best. It was also found that the n -propylamine derivative performed the best of the amine derivatives. The cloud point of this polymer derivative was found to be lower than ambient temperature, which is considered too low for practical oilfield applications. However, high cloud point PVDMA derivatives such as the ethylamine or pyrrolidine derivatives still gave reasonable KHI performance. The KHI performance of the n -propylamine derivative of PVDMA-I was tested at different concentrations in the range 1000–7000 ppm. It was found that the performance improved as the polymer concentration was increased. Highlights: A series of amine derivatives of poly(2-vinyl-4, 4-dimethylazlactone)s has been synthesized. The polymers have been investigated as kinetic hydrate inhibitors for the first time. Performance increased with decreasing molecular weight down to 1845 mol/g. The best performance was for the n-propylamine derivative.